Ladybird communities in rural woodlands: Does an invader dominate? - Farrow, Rachel A.; Roy, Helen E.; Brown, Peter M. J. (Frontiers in Conservation Science, 2022)
The invasive alien species Harmonia axyridis (Coleoptera: Coccinellidae) was first observed in the UK in 2004. Previous studies have demonstrated the adverse effects on other species of H. axyridis during its early stages of establishment. However, habitat factors are important in determining distribution and population trends of ladybirds. Whilst the abundance of H. axyridis is well known in the UK within urban and other managed habitats, much less is known about its abundance in the wider countryside. Here we present the results of surveys from rural woodland habitats to assess whether or not H. axyridis dominates coccinellid communities in these rural habitats. Additionally, we explored the relationship between coccinellid and aphid abundance within these habitats. All field sites were in Cambridgeshire or Suffolk, East Anglia, UK and were surveyed between May and October 2016 and 2017. Three deciduous sites and three coniferous sites were included in the study. Surveys were conducted using a standardised approach involving sweep-netting within grass margins and tree beating to sample ladybirds from trees. Three distinct vegetation structures or layers were surveyed within both the coniferous and deciduous sites; tree, shrub and herb layer. All captured coccinellids were identified to species-level. Seventeen species of coccinellid and over 1300 individuals were recorded during the study period from two distinct site types (deciduous, coniferous). Species richness was lower at deciduous sites (n = 12) in comparison to coniferous (n = 16) sites. The coccinellid community also did not appear to be dominated by H. axyridis at rural sites, in contrast to urban areas. Deciduous woodland appeared to be a lesser preferred habitat of H. axyridis than coniferous woodland. Additionally, there was a distinct difference in the coccinellid community in relation to vegetation structure (across the tree, shrub and herb layers) between coniferous and deciduous sites. Our results indicate that there appear to be distinct native coccinellid communities at deciduous and coniferous sites. We discuss the way in which rural woodlands could act as a refuge for some native coccinellids.